Dynamic Compatibility Control Method Research for AC-DC Locomotive under Low-voltage Condition - LUO Ji-guang; QIAO Xian-hua (机车电传动)
With traffic increasing, voltage of some electrified railway’s power-supply network was continuously reducing, which influenced locomotive normal operation. A little-cost and effective settling method was put forward from optimizing locomotive traction characteristics, implementation principle and scheme of which were introduced in detail.